Control of Biodegradability of Polyurethane Foam Based on Palm Oil by Ratio of Soft Segment on the Polymer Backbone - Haryono, Agus; Triwulandari, Evi; Sondari, Dewi; Randy, Ahmad; Ridwanuloh, Asep Muhamad (ANNALES BOGORIENSES, 2010)
Polyurethane  is  polymer  synthetic  which  is  formed  by  reaction  between  polyols  and  polyisocyanates.polyols  are  compounds  which  contain  two or  more  hydroxyl  groups.  Polyurethane  can  be  applied  in  various forms,  such  as  foam,  elastomeric,  coating  and  adhesive.  In  this  work,  we  developed  pol yurethane  foams  by using polyols  based  on  palm  oil.  Palm  oil  based  polyols  as  soft  segments  in  the  polyurethane  backbone accelerate biodegradable process of the polyurethane. Biodegradability is the ability of material to be utilized as a carbon source by  microorganisms and converted safely into carbon dioxide, biomass and water. Commercially available  polyurethane  foams  are  usually  produced  from  petrochemical  based  polyols  that  they  are  not biodegradable. The biodegradability study was conducted by using  Aspergillus niger  (fungi) and  Pseudomonas aeruginosa(bacteria),  with  variation  of  method  and  media  for  biodegradation.  Rigid  polyurethane  foam  was synthesized by  using  one  shoot  process  method,  which  is  reaction  between  palm based polyol  mixture  and methylene diphenly diisocyanate (MDI) at room temperature. The effect of variation of ratio of polyisocyanates (NCO) as hard segment and polyols (OH) as soft segment to the properties of polyurethane foams were studied in detail. Study of the effect NCO/OH ratio   was conducted with variation ratio of 0.8,  1.0  and  1.2. Increasing hard segment (NCO) ratio to the soft segment (OH) affected in the decreasing of hydrophilicity of foam. Thus,the penetration of water into bulk of polymer decreased. The biodegradability  of foam was also affected by the soft segment ratio on the polymer backbone.   Keywords: biodegradable, polyurethane, palm oil, polyols, soft segment